Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fimmu.2019.00116
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive CSF3R Deep Sequencing in Patients With Severe Congenital Neutropenia

Abstract: High frequency of acquired CSF3R (colony stimulating factor 3 receptor, granulocyte) mutations has been described in patients with severe congenital neutropenia (CN) at pre-leukemia stage and overt acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS). Here, we report the establishment of an ultra-sensitive deep sequencing of a CSF3R segment encoding the intracellular “critical region” of the G-CSFR known to be mutated in CN-MDS/AML patients. Using this method, we achieved a mutant allele frequency (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Let us emphasize that our initial and final fractions of mutant receptor data come from sequencing of samples from patients with SCN. Availability of these sequencing data in papers (Beekman et al, 2012;Skokowa et al, 2014;Klimiankou et al, 2019) is at the stem of our results.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Let us emphasize that our initial and final fractions of mutant receptor data come from sequencing of samples from patients with SCN. Availability of these sequencing data in papers (Beekman et al, 2012;Skokowa et al, 2014;Klimiankou et al, 2019) is at the stem of our results.…”
Section: Discussionmentioning
confidence: 91%
“…Changing this assumption leads to different estimates, as it can be tested by modifying the parameter λ in the spreadsheet (λ equals the inverse of the interdivision time). Overall, the estimates span a range from 0 to 0.05, with the exception of patient 13 of publication (Klimiankou et al, 2019) who has a negatively estimated selection coefficient. Figure 3 depicts estimated selection coefficientsŝ from Table 1, plotted against the time interval t 1 − t 0 between the first and the second instance of sequencing.…”
Section: Approximate Mean Expression Vs Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…HAX1 variants underlie some autosomal recessive forms and were found to be the underlying cause of SCN in the families originally described by Kostmann [5]. It has been suggested that these variants impair neutrophil maturation via defective CSF3R signaling as the number of G-CSF receptors on myeloid precursors of SCN patients is elevated and majority of SCN patients benefit from the administration of pharmacological doses of granulocyte colony stimulating factor (G-CSF) [6].…”
Section: Introductionmentioning
confidence: 99%